Grinding plastic mould steels using aluminium oxide wheel - Lau, Sze Wai. (2013)
Grinding is one of the most complex processes in machining. Usually it is used for the finishing process to obtain a good surface finish and accurate dimension to the product by removing small amount of material on the surface (Rowe, 2009). It can produce very fine finishes and very accurate dimensions with tolerance up to 5μm for flat material and 8μm for parallel surface (Wikipedia, 2013).The optimal surface finish can be obtained by varying several grinding system factors such as the grinding wheel characteristics, dressing conditions and machine parameters. Therefore it is important to study the effect of varying various grinding conditions on the work piece surface finish. The quality of the surface finish will be evaluated by analysing the grinding wheel surface and the work piece topography. Surface topography of the grinding wheel surfaces and work piece are measured in three dimensions using the surface stylus method.